Development of an Information System for Reporting Violations of Norms and Law in a Boarding House in Pabelan - Triyono, Agus; Amin, Choirul; Thoyibi, M (Journal of Community Services and Engagement: Voice of Community (VOC), 2023)
Data 2022 shows that the total number of UMS students is 36,712 students. With such a number, the impact on the high demand for temporary housing (kos). With this large number of boarding houses, violations of social rules and norms are also high. Based on this, this community service aims to develop an information system that makes it easier for members of the public to report violations. The methods used in this activity are situation analysis, system creation, socialization, and system handover. The results of the activity show that community service activities are going well with the main indicator, namely the information system has been successfully created and socialized to residents and the UMS Disciplinary Team. However, for its implementation, further coordination is still needed with Bagmawa UMS, as well as improving the system according to needs.